2007
DOI: 10.1590/s0036-46652007000500013
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of enteroparasites with molecular characterization of Cryptosporidium spp. in different Brazilian communities

Abstract: GONÇALVES, Elenice Messias do Nascimento-Incidência de enteroparasitas com caracterização molecular de Cryptosporidium spp. em diferentes comunidades brasileiras. São Paulo, 2007.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Multilocus genotyping of Cryptosporidium spp. associated with diarrhea outbreak in a day care unit by DNA sequencing analysis of fragments coding for 18S, COWP and a microssatelite locus (ML1) revealed the presence of C. hominis in all the 29 samples 4 . Cryptosporidium isolates identified in fourteen stool samples from five HIV patients and nine immunocompetent children revealed two C. parvum, eight C. hominis and two C. meleagridis 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multilocus genotyping of Cryptosporidium spp. associated with diarrhea outbreak in a day care unit by DNA sequencing analysis of fragments coding for 18S, COWP and a microssatelite locus (ML1) revealed the presence of C. hominis in all the 29 samples 4 . Cryptosporidium isolates identified in fourteen stool samples from five HIV patients and nine immunocompetent children revealed two C. parvum, eight C. hominis and two C. meleagridis 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, few studies on the relative frequency of Cryptosporidium genotypes found in humans have been published, with C. parvum and C. hominis being incriminated as the most prevalent genotypes 1,2,3,4,5 . In this paper, we aimed to reveal and discuss the relative frequencies of Cryptosporidium in human patients from an infectious diseases hospital in the municipality of São Paulo, São Paulo State, Brazil.…”
Section: Introductionmentioning
confidence: 99%